Catamenial Pneumothorax: Menstruation-Associated Pneumothorax - Jabłonowska, Magdalena; Grzeszczuk, Paulina; Kaczmarek , Aleksandra; Kaczmarek, Wojciech; Krakowiak, Magdalena (Quality in Sport, 2025)
Introduction: This article explores catamenial pneumothorax, a rare form of spontaneous pneumothorax linked to the menstrual cycle and most commonly associated with thoracic endometriosis syndrome. It discusses the current understanding of its epidemiology, pathophysiology, clinical presentation, diagnostic challenges, and treatment strategies. The discussion underscores the importance of accurate diagnosis and multidisciplinary treatment approaches to reduce recurrence and improve quality of life. Materials and Methods: A thorough literature search was performed using PubMed and Google Scholar databases with the following keywords: “catamenial pneumothorax”, “endometriosis”, “VATS”, “hormone therapy”. Summary: Catamenial pneumothorax (CP) is a rare, cyclical spontaneous pneumothorax occurring predominantly in reproductive-age women, often associated with thoracic endometriosis syndrome. Its exact pathophysiology remains unclear, but proposed mechanisms include metastatic spread of endometrial tissue, hormonal influences, and anatomical defects in the diaphragm, especially on the right side. Diagnosis relies on clinical suspicion, imaging, and video-assisted thoracoscopic surgery, while effective management typically involves surgical intervention combined with postoperative hormonal therapy to reduce recurrence. Conclusions: Catamenial pneumothorax is a significant clinical manifestation of thoracic endometriosis and should be considered in reproductive-age women presenting with recurrent pneumothorax correlated with their menstrual cycle. Optimal outcomes are achieved through a combination of video-assisted thoracoscopic surgery and postoperative hormonal therapy, supported by a multidisciplinary approach.